Invasive non-typhoidal Salmonella from stool samples of healthy human carriers are genetically similar to blood culture isolates: a report from the Democratic Republic of the Congo - Mbuyi-Kalonji, Lisette; Hardy, Liselotte; Mbuyamba, Jules; Phoba, Marie-France; Nkoji, Gaëlle; Mattheus, Wesley; Im, Justin; Marks, Florian; Jeon, Hyon Jin; Jacobs, Jan; Lunguya, Octavie (Frontiers in microbiology, 2023)
Invasive non-typhoidal Salmonella (iNTS) (serotypes Typhimurium and Enteritidis) are major causes of bloodstream infections in sub-Saharan Africa, but their reservoir is unknown. Aiming to demonstrate human carriers as a reservoir, we assessed an iNTS disease endemic rural community (Kikonka health area, Democratic Republic of the Congo) for intestinal carriage of iNTS. After a census, healthy subjects from randomly selected households provided three successive stool samples forSalmonella culture. We next compared the stool isolates for genetic relatedness with time and health area-matched blood culture isolates obtained from hospitalized patients by multiple locus variable-number tandem repeat analysis (MLVA) and performed whole genome sequencing (WGS) on a subset of stool and blood isolates. Among 2,354 eligible subjects, 2,234 (94.9%) consented and provided at least one stool sample, and 2,219 (94.3%) provided three stool samples. The cumulative proportion of Salmonella carriers after 3 days was 4.4% (n = 98). S. Typhimurium and Enteritidis were found in 26 and 3 carriers, respectively, representing 1.3% (29 out of 2,234) of participants living in 6.0% (26 out of 482) of households. MLVA types of all 26 S. Typhimurium stool isolates matched with the corresponding MLVA types of blood isolates. The MLVA type of one out of three Enteritidis stool isolates matched the single MLVA type of the five Enteritidis blood isolates. WGS analysis of S. Typhimurium (n = 20) and S. Enteritidis (n = 4) isolates revealed Typhimurium multilocus sequence type (ST)313 Lineage 2 and Enteritidis ST11 Central/Eastern African and Outlier clades and confirmed the MLVA clustering. More than three-quarters of Typhimurium isolates showed combined multidrug resistance, ceftriaxone resistance, and fluoroquinolone non-susceptibility. In conclusion, the present study demonstrated iNTS carriage among healthy community members, with stool isolates that were genetically similar to blood culture isolates obtained in patients from the same community. These findings contribute to the evidence of a human reservoir of iNTS.
Gesehen am 27.06.2024